Extensional viscosity: A critical discussion - Petrie, Christopher J.S.
The issue of whether extensional viscosity is a concept that causes more confusion than enlightenment is addressed. This author's view is that misuse of the concept certainly has caused much confusion and, although it is in principle a simple and straightforward idea, it continues to be misused. What is straightforward is the formal definition of extensional viscosity, for steady uniform extensional flow. What gives rise to confusion is the careless use of measurements in flows which are not both steady and spatially uniform.
Keywords: TROUTON; EXTENSIONAL VISCOSITY; EXTENSIONAL FLOW; HISTORY; REVIEW